The everything kids' scratch coding book ebook Learn to code and create your own cool games!. - Rukman, Jason (Everything Kids., 2018)
Teach kids the concepts of coding in easy-to-understand language and help them develop games of their own with The Everything Kids' Scratch Coding Book ! Understanding computer science is becoming a necessity in the modern age. As our world shifts towards becoming increasingly more technical and automated, the ability to code and understand computers has become one of the most valuable skills any child can have on the road to a successful life. More and more schools are recognizing this importance and have started to implement computer science and coding as core elements in their curriculums, right alongside math and history. The Everything Kids' Scratch Coding Book helps children get a head start on this new essential skill, with Scratch coding—a language designed by MIT specifically to help a younger audience learn to code. In no time, children will learn basic coding concepts, build fun games, and get a competitive edge on their classmates. This book encourages children to think analytically and problem-solve, while helping them develop an essential skill that will last them a lifetime.